Criminal Law Enforcement Policies In Prevention Efforts Of Information Technology Crime - Vitriano Aditya Morradi; Munsharif Abdul Chalim (Jurnal Daulat Hukum, 2019)
The problem of this research is the criminal law enforcement policies in prevention efforts of information technology crime in the positive law and criminal law enforcement policy in combating criminal acts in the positive law of information technology that will come. The method used is normative juridical approach and specification in this study were included descriptive analysis. And sources and types of data in this research is secondary data obtained from the study of literature relating to the theory of Enforcement and Compliance Laws. Based on the results of the research that the Indonesian government policy with the promulgation of Act No. 11 of 2008 on Information and Electronic Transactions (ITE Act.) is the first legal framework that governs the world of cyber (Cyber Law) because the charge and broad scope in discussing arrangements in cyberspace, such as the expansion of electronic evidence together with the evidence that has been known so far, the recognition of electronic signatures as a means of verification, and authentication of legitimate an electronic document, as well as setting deeds done in cyberspace as a criminal offense. Policy formulation of the crime of information technology should pay attention to the internal harmonization with the criminal justice system or the general sentencing rules that apply today. It can not be said to harmonization / synchronization when the formulation policies are outside the system. Therefore the policy formulation of criminal law the crime of information technology in the future should be in the criminal justice system currently applies.Keywords: Policy, Law Enforcement; Criminal; Information Technology.